The culture of catfish (Clarias Macrocephalus) Gunther - Shiro, Hara. ((Japan Overseas Cooperative Volunteers) Philippines, 1977)
Fish culture in the Philippines is presently dominated by the milkfish species. A vast area of the country's inland waters, particularly the brackish waters is occupied by the milkfish industry. Because of this, milkfish and its biology and culture has been the general subject of many scientific pursuits in most of the countries government institutions engaged on researches in the filed of aquaculture. Recently, however, the catfish has also gained some popularity. It has been a well-relished fish in some parts of the Philippines and commands a very good price in the market today. It seemed to be promising economic species in the country is presently wanting. Generally, available literatures on its technology were very few mostly based on the Thai method which actually deals on the culture if clarias batrachus. But the more acceptable species of catfish in the Philippines is the clarias macrocephalus. It is this problem that inspired the author to work on this species for several years, whish started back in 1972. In this paper, actual experiences on the culture clarias macrocephalus in the country and observations on the Thai method based on a recent trip of the author to Thailand in presented. The chapter on the feeding of catfish is a very short one and presents only a very limited scope because experiments on this aspect was conducted during the later part of the work. This chapter, however, is one of the most important. It is hoped that future researchers on this species will give emphasis on the feeding problem. One of the limitations of this paper is the author's negligence to collect enough data made by other researchers on this species. The reader's criticism will, however, be highly appreciated.
Keywords: Catfishes; Clarias macrocephalus (Gunther)